Gambaran border dan periosteal reaction lesi rahang pada radiograf - Aga Satria Nurrachman; Farina Pramanik; Azhari Azhari; Lusi Epsilawati (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: Understanding the differences of general signs and typical characteristics of a lesion in radiograph is constantly important for dentists to determine the nature of a lesion. Some signs that can be observed more specifically were the presence of periosteal reaction and the border of existing lesions. These differences may be taken into consideration to define the diagnosis and type of the lesion. The purpose of this article is to provide an overview of the radiographic features of periosteal reaction and border in jaw lesions. Literature Review: This article is a literature review which discussed several articles relating to the radiographic features of border and periosteal reaction in various jaw lesions. Based on this review, there were different features of border, where each lesion had its own borderline that differs between cystic, benign and malignant properties. While the picture of periosteal reaction indicates the extent to which the lesion involves cortical tissue in the bone. Conclusion: The conclusion is that the border image and periosteal reaction can be one of the typical markers in determining jaw lesions.